Dying of mesothelioma: A qualitative exploration of caregiver experiences. (20th June 2022) - Lee, Jessica T.; Mittal, Dipti L.; Warby, Anne; Kao, Steven; Dhillon, Haryana M.; Vardy, Janette L.
Abstract: Objective: To explore the experience of family caregivers of people with mesothelioma with focus on end‐of‐life issues. Methods: A qualitative sub‐study using semi‐structured interviews and thematic analysis. Results: Fourteen caregivers were interviewed; 11 were bereaved. The overarching theme was the impact of patients' diagnosis, treatment and death on caregivers and families. Three main themes were identified: (i) information provision and decision‐making; (ii) grief and bereavement; and (iii) involvement and timing of palliative care. Caregivers initially had minimal knowledge of mesothelioma and wanted more information. Prognostic uncertainty caused distress. Grief and bereavement sub‐themes were (i) coping and personal priorities; (ii) reflections on dying; and (iii) reflections on care. Caregivers highlighted the importance of creating meaningful events, having hope, 'doing something' and support from family and external sources. Reflections on dying contrasted regret after a 'bad', often unexpected death, with 'good' deaths. Care was made difficult by challenges navigating the health system and perceived gaps. Caregivers reported late referral to palliative care. Conclusion: Lack of information caused challenges for caregivers. Grief and bereavement outcomes varied and may have been adversely impacted by lack of engagement with palliative care. Integrated care with lung cancer coordinators and improved palliative care access may reduce caregiver burden.